1998
DOI: 10.1046/j.1365-3083.1998.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Brain Lesion Affects the Lateralization of T‐Lymphocyte Dependent Cutaneous Inflammation. Evidence for an Immunoregulatory Role of the Right Frontal Cortex–Putamen Region

Abstract: Localization of the Brain Lesion Affects the Lateralization of T-lymphocyte Dependent CutaneousInflammation. Evidence for an Immunoregulatory Role of the Right Frontal Cortex-putamen Region. Tarkowski E, Jensen C, Ekholm S, Ekelund P, Blomstrand C, Tarkowski A. Scand J Immunol 1998;47:30-36 We have previously demonstrated that brain lesions caused by stroke led to the lateralization of T-cell dependent inflammation. The purpose of this study was to assess the impact of localization of the brain lesion on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Whether the CVA was distant or recent likewise did not seem to affect the skin response to DHT. These results are at variance with those of Tarkowski et al (2)(3)(4)(5)13). However, the lateralization of the PPD response in the studies of Tarkowski et al mainly appeared in subgroup analyses.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Whether the CVA was distant or recent likewise did not seem to affect the skin response to DHT. These results are at variance with those of Tarkowski et al (2)(3)(4)(5)13). However, the lateralization of the PPD response in the studies of Tarkowski et al mainly appeared in subgroup analyses.…”
Section: Discussionsupporting
confidence: 72%
“…Lymphoid tissue in the spleen and lymph nodes is innervated by autonomic nerve fibers, and lymphocytes possess receptors for neuropeptides and neurotransmitters (2). Whether immune responsiveness varies between areas with intact and impaired innervation is a question that has been studied in subjects with unilateral cerebrovascular accident (CVA) (2)(3)(4)(5). In these European studies, purified protein derivative (PPD) of tuberculin was administered in both arms of each subject, and the cutaneous delayed-type hypersensitivity (DTH) response was used as a measure of antigen-specific T-lymphocyte reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interestingly, some small studies found a localization-dependent pattern in immune dysfunction after stroke. 27,28 However, others did not confirm this finding. 29 More importantly, previous studies investigated patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 91%
“…The results of the regulatory effect of the asymmetry of brain hemispheres on cellular reactions were obtained by other authors, too. Tarkowski et al [28,29] demonstrated that patients with a stroke with left hemiparesis had a significantly greater DTH response on the affected side than patients with right hemiparesis. While conducting a more detailed study, the authors showed that infarcts encompassing the frontal lobe-putamen led to significantly large DTH responses on the paretic side compared to the contralateral side.…”
Section: Discussionmentioning
confidence: 99%